THE EFECTIVENESS OF PICTORIAL READING IN IMPROVING STUDENTS’ READING INTEREST TO THE 7TH-GRADE STUDENTS OF MTS N 1 GROBOGAN IN THE ACADEMIC YEAR 2022-2023 - Dwi Widi Astuti (Berajah Journal, 2022)
This research was conducted to know the effectiveness of using pictorial reading in improving students’ reading interest in MTS N 1 Grobogan. This research was a quantitative design method with a quasi-experimental design. There were 2 classes used in this research, the experimental group which was taught with pictorial reading, and the control group which was taught without pictorial reading. The result of this research shows that there was a significant difference between both classes. It can be seen from the data analysis by using a t-test. T-value is 11,3430600014, with a level of significance of 5% with df 58, the t_table is 2,001. It shows that t-value>t-table. So, Na is rejected, and Ha is accepted. The mean of students’ post-test scores in the control group was 62,83, and the mean of students’ post-test scores in the experimental group was 80. So, it can be concluded that there is a significant difference between the students’ reading interests who were taught with pictorial reading and the students’ reading interests who were taught without pictorial reading.